One-year outcome of a lumboperitoneal shunt in older adults with idiopathic normal pressure hydrocephalus - Fang, Xuhao; Deng, Yao; Xu, Xinxin; Shu, Weiquan; Tang, Feng; Li, Shihong; Zhu, Ting; Zhang, Li; Zhong, Ping; Mao, Renling (Frontiers in surgery, 2022)
Lumboperitoneal shunt (LPS) is now an effective surgical modality for idiopathic normal pressure hydrocephalus (iNPH), but there is still a lack of clinical data on LPS in older adult iNPH patients in China. We aim to report the shunt effect and the complications of older adult iNPH patients treated with LPS at a single center in Shanghai, China.BackgroundLumboperitoneal shunt (LPS) is now an effective surgical modality for idiopathic normal pressure hydrocephalus (iNPH), but there is still a lack of clinical data on LPS in older adult iNPH patients in China. We aim to report the shunt effect and the complications of older adult iNPH patients treated with LPS at a single center in Shanghai, China.We conducted a retrospective study among adults over 60 years old who were diagnosed as iNPH and treated with LPS from September 2016 to December 2020. The shunt effect was evaluated from two dimensions of functional and symptomatic improvement 3 months and 1 year after surgery, respectively. The potential factors related to the shunt effect one year after surgery were explored by comparing the effect between different subgroups and conducting multivariate logistic regression analysis.MethodsWe conducted a retrospective study among adults over 60 years old who were diagnosed as iNPH and treated with LPS from September 2016 to December 2020. The shunt effect was evaluated from two dimensions of functional and symptomatic improvement 3 months and 1 year after surgery, respectively. The potential factors related to the shunt effect one year after surgery were explored by comparing the effect between different subgroups and conducting multivariate logistic regression analysis.A total of 85 patients were included in this study, ranging from 60 to 93 years old, with an average age of 74.7. The function and symptoms were better both 3 months and 1 year after surgery than before (P < 0.001). At the 1-year postoperation follow-up, the functional and symptomatic improvement rates were 72.9% and 90.6%, respectively. The symptomatic improvement rates of gait, urination, and cognition were 74.1%, 72.9%, and 60.0%, respectively. Multivariate logistic regression analysis showed that improvement in function was much more possible in patients with less than 24 months from symptom onset to surgery (OR = 24.57, P < 0.001) and those with disproportionately enlarged subarachnoid-space hydrocephalus (OR = 5.88, P = 0.048); improvement in gait was also more possible in patients with less than 24 months from symptom onset to surgery (OR = 5.29, P = 0.017); improvement in urination was more possible in patients with diabetes (OR = 4.76, P = 0.019), and improvement in cognition was more possible in patients with preoperative modified Rankin scale level lower than 4 (OR = 3.51, P = 0.040). Minor operation-related complications were seen in 27 patients (31.8%) and severe complications in 6 patients (7.1%).ResultA total of 85 patients were included in this study, ranging from 60 to 93 years old, with an average age of 74.7. The function and symptoms were better both 3 months and 1 year after surgery than before (P < 0.001). At the 1-year postoperation follow-up, the functional and symptomatic improvement rates were 72.9% and 90.6%, respectively. The symptomatic improvement rates of gait, urination, and cognition were 74.1%, 72.9%, and 60.0%, respectively. Multivariate logistic regression analysis showed that improvement in function was much more possible in patients with less than 24 months from symptom onset to surgery (OR = 24.57, P < 0.001) and those with disproportionately enlarged subarachnoid-space hydrocephalus (OR = 5.88, P = 0.048); improvement in gait was also more possible in patients with less than 24 months from symptom onset to surgery (OR = 5.29, P = 0.017); improvement in urination was more possible in patients with diabetes (OR = 4.76, P = 0.019), and improvement in cognition was more possible in patients with preoperative modified Rankin scale level lower than 4 (OR = 3.51, P = 0.040). Minor operation-related complications were seen in 27 patients (31.8%) and severe complications in 6 patients (7.1%).LPS could improve the function and symptoms of older adult iNPH patients. Early detection, diagnosis, and treatment of the disease could improve the shunt effect of the patients. Older adult iNPH patients with higher age ranges could achieve comparable shunt results compared with younger adults.ConclusionLPS could improve the function and symptoms of older adult iNPH patients. Early detection, diagnosis, and treatment of the disease could improve the shunt effect of the patients. Older adult iNPH patients with higher age ranges could achieve comparable shunt results compared with younger adults.